Nonlinear control approaches for an underactuated control moment gyroscope. - Toriumi, Fabio Yukio (2020)
Control moment gyroscopes (CMG) are widely used as actuators in some important applications, as the attitude control of spacecraft and satellites, due to its interesting and advantageous characteristics, such as its efficient high output torque capability. Motivated by this, we explore here a CMG unit, model 750, from Educational Control Products (ECP), which is a complex and versatile system that can operate in both single-input/single-output (SISO) and multiple-input/multiple-output (MIMO) configurations. This underactuated electromechanical plant presents a highly coupled nonlinear dynamics with a wide operating range, posing additional challenges to the control design, due to the fact that the outputs to be controlled are unactuated states of the system and its tracking task involves time-varying trajectories. To deal with these challenges, three nonlinear control approaches, the feedback linearization (FL), sliding-mode (SM), and passivity-based (PB), are proposed to improve the performance of the ECP CMG tracking task and get a wider operating range. Since nonlinear control approaches are critically dependent on the system model, the CMG modeling process based on Gibbs-Appell method and Kane\'s dynamical equations is firstly developed, then its nonlinear model is explicitly presented and used for both controller designs and numerical simulations. Next, the application of the three nonlinear control approaches to the tracking task of a class of fully-actuated systems is briefly presented, followed by the specific issues inherent to the CMG underactuation. To overcome this problem, the CMG intrinsic reaction torques are employed in the three controller designs. Simulation and experiment results are considered to validate the effectiveness of the controllers and the final results are compared to each other for an overall discussion, where the maximum absolute error (MAE) and the integral absolute error (IAE) indexes are presented to corroborate the performance analysis.